Implementasi Komponen Manajemen Berbasis Sekolah pada Jenjang Pendidikan Anak Usia Dini: Tinjauan Pustaka Sistematis - Ginting, Septiana Br; Mustapa, Noviana; Aisyah, Siti; Maharani, Laila (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
The concept of School-Based Management (SBM) has emerged as a key strategy for improving the quality of education in the context of regional autonomy. It offers potential solutions to various challenges faced by educational institutions. A systematic literature review was conducted to analyze the components of school-based management that have been discussed, researched or evaluated at the early childhood education institution level over the past decade (2019-2024). A total of nine studies were included in this review and it was found that principals' professionalism, teachers' performance, curriculum development, learning methods and innovations, learners' potential, procurement of facilities and infrastructure, control of school operational costs, school programs, school and community partnerships and school culture and character were discussed aspects in the implementation of school-based management. This review also shows positive views and evaluations of the implementation of school-based management elements. In addition, the results show that the implementation of the components of school-based management improves the quality of the education unit. However, more in-depth studies will be needed in the future to provide authors with clear guidelines for assessing the implementation of school-based management at the specific education unit level.